2015
DOI: 10.1109/tap.2015.2478443
|View full text |Cite
|
Sign up to set email alerts
|

A Wideband Resistive Beam-Splitter Screen

Abstract: We present the design, construction and measurements of the electromagnetic performance of a wideband space beam splitter. The beam splitter is a sheet in free space that is designed to divide incident radiation into reflected and transmitted components for interferometer measurement of spectral features in the mean cosmic radio background. Analysis of a 2element interferometer configuration with a vertical beam splitter between a pair of antennas leads to the requirement that the beam splitter be a resistive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 12 publications
2
14
0
Order By: Relevance
“…This coherence would be well above that without a beam splitter in between. The performance of space beam splitters was analyzed in Mahesh et al (2015) where it was shown that the sheet impedance was required to be resistive and of value half the impedance of free space (377/2Ω) for maximum coherence and hence interferometer response. Mahesh et al (2015) also proposed a method for the construction of such a screen as a resistor grid, Figure 7.…”
Section: Enhancement Of the Spatial Coherencementioning
confidence: 99%
See 4 more Smart Citations
“…This coherence would be well above that without a beam splitter in between. The performance of space beam splitters was analyzed in Mahesh et al (2015) where it was shown that the sheet impedance was required to be resistive and of value half the impedance of free space (377/2Ω) for maximum coherence and hence interferometer response. Mahesh et al (2015) also proposed a method for the construction of such a screen as a resistor grid, Figure 7.…”
Section: Enhancement Of the Spatial Coherencementioning
confidence: 99%
“…The performance of space beam splitters was analyzed in Mahesh et al (2015) where it was shown that the sheet impedance was required to be resistive and of value half the impedance of free space (377/2Ω) for maximum coherence and hence interferometer response. Mahesh et al (2015) also proposed a method for the construction of such a screen as a resistor grid, Figure 7. Schematic of a configuration with a beam splitter sheet in between the interferometer elements (Mahesh et al 2015).…”
Section: Enhancement Of the Spatial Coherencementioning
confidence: 99%
See 3 more Smart Citations